Aumento da eficiência na captação de raios solares na produção de energia elétrica em células fotovoltaicas, por meio de um seguidor solar - Dantas Neto, Pedro Moises (Universidade Federal Rural do Semi-Árido, 2018)
Research in the field of renewable energy has grown since the oil crisis of 1973 to meet the need for energy in a sustainable way. Solar energy as a renewable energy has been obtained with the possibility of quick compensation with a long term. One of the ways to improve the acquisition of photovoltaic energy would be to increase the rate of photocells, such as the one made in this work with a movement capable of maintaining a greater time interval in the rotation of the solar rays in the photovoltaic. Through a control made with arduino, to drive a servo motor from the light intensity captured by light sensors. The results were satisfactory, presenting an increase of about 15% in relation to the fixed systems, proven or increased efficiency in the capture of the photocells.
Monografia
Keywords: Energia solar; Seguidor solar; Sistemas fotovoltaicos; Painéis fotovoltaicos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA